The Terminology of "Al-Siyaq" between the Ancients and Moderns (Linguistic, Balaghah, and Ushul Studies) - Ahmed, Mohamed Salah El-Din; Salem, Elsayed Mohamed; Mahdi, Rijal (Borneo Journal of Language and Education, 2024)
The importance of this research is centered on the necessity of studying common, thorny terms in Arab and Islamic sciences. Perhaps the most prominent of these terms is “context.” Context is not a loose term as it seems, but it is a term of great specificity and importance in multiple sciences. Which prompted the researchers to study its linguistic and terminological significance, and its interpretation among the ancients and moderns. The research aimed to: clarify what is meant by context linguistically and terminologically among the ancients and moderns, present and define the terms that are associated with the concept of context in the Arab and Islamic sciences, and investigate the significance of that term and edit its concept in the various arts that It is widely used, and the research has adopted several approaches to reach its desired goals. He adopted the historical and investigative approaches in tracing the term context among the ancients and moderns in the sciences that used it. He also adopted the analytical and deductive approaches in analyzing the definitions of this term and the terms that come into contact with it. To liberate the concept of context among the ancients and moderns; This is to reach a number of results, the most important of which are: The ancient scholars of the nation - may God Almighty have mercy on them - did not prefer a clear definition of context when they studied any of the arts that used that term, nor did the modern scholars agree on a single definition of context during its circulation as a term in a number of Arab and Islamic sciences. The research was able to collect the definitions of the term “context” by collecting various definitions of terms that came into contact with the term “context” and were linked to it, explaining what was meant by that term among the ancients, and liberating the term “context” among the ancients through their talk about it and their use of it. The research was also able to collect the most important definitions. The innovators of that term, with distinction and comparison between them in terms of combination and prevention.